Modulation of Motoneuronal Activity With Sleep-Wake States and Motoneuronal Gene Expression Vary With Circadian Rest-Activity Cycle - Herr, Kate B.; Mann, Graziella L.; Kubin, Leszek (Frontiers in Integrative Neuroscience, 2018)
In both nocturnal and diurnal mammals, sleep and wake states differentially aggregate during the rest and active phases of circadian cycle. Closely associated with this rhythm are prominent changes in motor activity. Here, we quantified the magnitudes of electromyographic activity (EMG) measured separately during different sleep-wake states across the rest-activity cycle, thereby separating amplitude measurements from the known dependence of the timing of wake and sleep on the phase of circadian rest-activity cycle. In 7 rats chronically instrumented for electroencephalogram and EMG monitoring, nuchal and lingual muscle EMGs were measured as a commonly used postural output in behavioral sleep studies and as a cranial motor output with potential clinical relevance in obstructive sleep apnea syndrome, respectively. We found that, for both motor outputs, EMG measured during wake episodes was significantly higher during the active phase, than during the rest phase, of circadian cycle. The corresponding patterns observed during slow-wave sleep (SWS) and rapid eye movement sleep (REMS) were different. During SWS, lingual EMG was very low and did not differ between the rest and active phase, whereas nuchal EMG had pattern similar to that during wakefulness. During REMS, lingual EMG was, paradoxically, higher during the rest phase due to increased twitching activity, whereas nuchal EMG was very low throughout the rest and active periods (postural atonia). In the follow-up comparison of differences in transcript levels in tissue samples obtained from the medullary hypoglossal motor nucleus and inferior olive at rest onset and active period onset conducted using microarrays, we identified significant differences for multiple transcripts representing the core members of the molecular circadian clock and other genes important for the regulation of cell metabolism and activity (up to n=130 at p<0.001). Collectively, our data indicate that activity of motoneurons is regulated to optimally align it with the rest-activity cycle, with the process possibly involving transcriptional mechanisms at the motoneuronal level. Our data also suggest that obstructive sleep apnea patients may be relatively better protected against sleep-related upper airway obstructions during REMS episodes generated during the rest phase, than during active phase, of the circadian cycle.